The Jacob Story: Between Oral and Written Modes. Issue 1 (2nd January 2019) - Na'aman, Nadav
ABSTRACT: In this article I examine the relations between Jacob's putative oral story and the pre-Priestly narrative. I argue that Hosea's prophecy presents the version of Jacob's oral story related in his time and antedated by many years the composition of the story-cycle in its written form. Comparison of Hosea's prophecy and Jacob's narrative indicates the thorough way in which the exilic author worked the oral story he received in order to fit it to his ideological messages and religious concepts. To further examine the relations between the oral and written modes, I discuss the episode of the treaty between Laban and Jacob (Gen 31, 45–54) in light of a Mari letter (A.3592). Comparison of the two episodes indicates that part of the biblical narrative rests on the oral story and other part was written by the late author. Evidently, the long process of oral transmission, the growth of the narratives in its course, and the creative reworking of the author make it impossible to either isolate the early oral layer within the present story-cycle or to date the stages of its growth in the oral process of transmission.